Blood, Bodies, and Violence: Gender and Women's Embodied Agency in the Egyptian Uprisings. - Bogert, Kathrine Van Den (Frontiers: A Journal of Women Studies, 2019)
The article focuses on gender and women's embodied agency in the Egyptian Uprisings held in Tahrir Square in Cairo, Egypt. It mentions relation to counter-revolutionary discourses and violence from regime and then the military regime, and less in relation to the specific political circumstances, like the elections. It also mentions violence was oft en gendered and sexualized and police to sexually harass and touch female protestors and their virginity tests.